МАТЕМАТИЧЕСКОЕ МОДЕЛИРОВАНИЕ ЭЛЕКТРОМЕХАНИЧЕСКИХ СИСТЕМ СТАНОВ ХОЛОДНОЙ ПРОКАТКИ - Назарова, Е.С. (Інститут електродинаміки НАН України, Київ, 2015)
Article is devoted to the potential of mathematical simulation of electromechanical systems of cold rolling mills in order to reduce energy consumption in the modernization of existing and designing new systems of automatic control of electric drives of these mills. Using the developed complex computer models of the rolling production elements, improved automatic control system of strip tension of cold rolling mill, the example of the synthesized optimal control system interconnected electric drives of winder and stand of a temper mill 1700-1 single stand cold rolling shop №1 JSC "Zaporizhstal". The application of optimal control system of strip tension will improve the quality control and provide energy-saving effect due to its insensitivity to a number of destabilizing factors, the lack of deregulation, the compensation effect of elastic long shaft and rolled strip on the dynamic characteristics of the drive. References 11, figures 5.